A novel approach to prepare Bi2Fe4O9 flower-like spheres with enhanced photocatalytic performance - Haibo Yang (Nature Portfolio, 2017)
Abstract A novel two-step approach consisting of hydrothermal process and subsequently selective etching has been developed to prepare flower-like three-dimensional porous Bi2Fe4O9 spheres with good uniformity and highly photocatalytic performance. XRD patterns and SEM images reveal that the Bi2Fe4O9 phase does not exhibit any changes after the etching process, and the crystal morphology evolves from micro-platelets to flower-like three-dimensional porous Bi2Fe4O9 spheres by controlling the experiment parameters. The change of morphology will lead to the significant increase of specific surface area, which would be beneficial to the enhancement of photocatalytic performance owing to prominent absorption in the ultraviolet and visible light region. As compared to Bi2Fe4O9 microplatelets, flower-like three-dimensional porous Bi2Fe4O9 spheres exhibit excellent photocatalytic degration rate of methyl orange (MO).